2006
DOI: 10.1002/jmv.20546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological features of non-breakthrough and severe exacerbation due to lamivudine-resistant hepatitis B virus mutants

Abstract: Patients who develop YMDD mutant during lamivudine therapy for hepatitis B virus (HBV) infection exhibit various clinical courses. Some patients show normal ALT levels, whereas others develop severe hepatitis exacerbations (SHEs) due to YMDD mutants. We studied 136 patients with YMDD mutant among 362 Japanese adult patients on lamivudine therapy. Clinical and virological features of patients without elevated HBV DNA after emergence of YMDD mutant (non-elevated group) were investigated. Moreover, virological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…During treatment, nucleotide sequences of the polymerase gene were determined by polymerase chain reaction (PCR) direct sequencing, as previously described 14. The viral polymerase reverse transcriptase (rt) gene at the baseline of LAM treatment (September 2006) showed the wild type sequence (with no LAM, ADV, ETV, or TDF resistance substitutions).…”
Section: Case Reportmentioning
confidence: 99%
“…During treatment, nucleotide sequences of the polymerase gene were determined by polymerase chain reaction (PCR) direct sequencing, as previously described 14. The viral polymerase reverse transcriptase (rt) gene at the baseline of LAM treatment (September 2006) showed the wild type sequence (with no LAM, ADV, ETV, or TDF resistance substitutions).…”
Section: Case Reportmentioning
confidence: 99%
“…However, the viral factors that may influence the severity of this hepatitis remain to be clarified. A recent study indicated that patients with a normal ALT level even after the emergence of a YMDD motif mutant are characterized by HBeAg negativity during pretreatment, HBeAg loss during therapy, a longer duration from the commencement of therapy until the emergence of YMDD mutant, and lack of mixed-type YMDD mutants [26] . In contrast, patients with severely exacerbated hepatitis after the emergence of a YMDD mutant tend to have more substitutions in the reverse transcriptase (rt) region within the polymerase gene at the time of hepatitis exacerbation than those without hepatitis exacerbation [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of amino acid mutation of polymerase is high in patients with hepatitis, no specifi c mutation has been observed. 12 The case of a patient who was LAM-resistant despite the absence of mutation in the YMDD motif was reported recently. The 181st alanine (A) in the Pol domain was replaced by threonine (T) (rtA181T) in this patient.…”
Section: Emergence Of Antiviral Resistance In Hbv Infectionmentioning
confidence: 95%